Russelll Simmons appointed (Raton Range Raton, NM 87740, 1981)
Newspaper article on Russell Simmons being appointed on the Mayor's Commission on Aging.
Master list item #: 5
File location is in the Raton file Cabinet
Keywords: Simmons, Russell; Raton ACity Commission; Raton Senior Center; Local History; Biography; Mayor; Seniors; Raton, New Mexico